Growth and Yield of Upland Rice Under Intercropping System with Soybean in Sandy Coastal Area - Fajrin Pramana Putra; Prapto Yudono; Sriyanto Waluyo (Jurnal Ilmu Pertanian, 2017)
Sandy coastal area in Indonesia is potential for upland rice cultivation, but it has constraints low of nutrient availability such as nitrogen. To solve the low fertility of the sandy land can be done by planting soybean between upland rice under intercropping system due to the soybean is able to provide nitrogen in soil through fixation of N2 in the air by root nodules. Intercropping is an alternative cropping system to increase land productivity, but there is competition between crops under an intercropping system. Reducing of the competition on the system is needed by crops proportion adjustment. The objective of the study is to examine growth and yield component of upland rice at different crops proportion under an intercropping system with soybean in the sandy coastal area. The research was conducted in Samas sandy coastal area, Bantul, Yogyakarta. This research used randomized complete block design (RCBD) with one factor and three blocks. The treatment of this research was five level crops proportion between upland rice and soybean under intercropping system, namely: 100:0; 80:20; 60:40; 40:60; and 20:80, respectively. The results showed that crop growth rate and yield per clump of upland rice increased on crops proportion adjustment under intercropping system with soybean. The crops proportion of 60:40 and 40:60 gave higher crop growth rates that were 1.45 g.dm-2.wk-1 and 1.44 1.45 g.dm-2.wk-1 than upland rice under monoculture (100:0) that was 1.09 g.dm-2.wk-1. The higher crop growth rates in crops proportion of 60:40 and 40:60 were able to give better yield per clump than other that were 17.17 g and 16.46 g, respectively. The yield of upland rice was not different under crops proportion of 100:0, 80:20, and 60:40 and decreased of upland rice proportion until ≤ 40% affected the low yield of upland rice.